Major paths of development in cultural animation. From social to personal animation - Wiesław Andrzej Żardecki (Maria Curie-Skłodowska University, Lublin, Poland, 2020)
The paper provides an overview of changes in cultural animation and general characteristics of its paths of development during specific periods, in view of the social, political, cultural and educational changes. While determining the unique human and social, as well as philosophical background of animation, the authors referred to premises relating to underlying qualities of modern industrial societies and man of the industrial age. The main body of the paper was devoted to reconstruction of cultural animation developments in view of cultural changes, and to presentation of a multi-faceted theoretical and practical approach to cultural animation over the past few decades. This served as the background for outlining a personalistic concept of cultural animation, focused on creating conditions conducive to personal development and self-fulfilment of humans. In the light of the study, cultural animation has seen the major shift from focus on opposing elite culture to multiplicity of its contemporary paradigms which, to a considerable extent, share the same approaches and main intentions. The paper is intended to methodize the examined issue, or rather to collect the material allowing to correctly classify the phenomena underlying the developments in cultural animation.